Newman’s Vision of a University: Then and Now - Heft, SM, James L. (Catholic Education: A Journal of Inquiry and Practice, 2007)
Catholic universities face many challenges today. Increasing secularization, faculty salaries, external funding, Catholic identity, academic freedom, and institutional autonomy are among the most prominent. This essay examines the contributions of John Henry Newman to Catholic higher education and argues for their relevance today.